Synthesis, In Silico Logp Study, and In Vivo Analgesic Activity of Analogs of Tetrapeptide FELL - Boryana Borisova; Hristina Nocheva; Stéphane Gérard; Marie Laronze-Cochard; Stefan Dobrev; Silvia Angelova; Stoyko Petrin; Dancho Danalev (MDPI AG, 2023)
Background: The inflammatory process represents a specific response of the organism's immune system. More often, it is related to the rising pain in the affected area. Independently of its origin, pain represents a complex and multidimensional acute or chronic subjective unpleasant perception. Currently, medical doctors prescribe various analgesics for pain treatment, but unfortunately, many of them have adverse effects or are not strong enough to suppress the pain. Thus, the search for new pain-relieving medical drugs continues. Methods: New tetrapeptide analogs of FELL with a generaanalgesic-Glu-X3-X4-Z, where X = Nle, Ile, or Val and Z = NH2 or COOH, containing different hydrophobic amino acids at positions 3 and 4, were synthesized by means of standard solid-phase peptide synthesis using the Fmoc/OtBu strategy in order to study the influence of structure and hydrophobicity on the analgesic activity. The purity of all compounds was monitored by HPLC, and their structures were proven by ESI-MS. Logp values (partition coefficient in octanol/water) for FELL analogs were calculated. Analgesic activity was examined by the Paw-pressure test (Randall-Selitto test). Results: The obtained results reveal that Leu is the best choice as a hydrophobic amino acid in the FELL structure. Conclusions: The best analgesic activity is found in the parent compound FELL and its C-terminal amide analog.